The Correlation Between Mastery of Qur’anic Vocabulary and Arabic Vocabulary Skills Among Islamic Senior High School Students - Rafli Syahzuldwiki; Saiful Islam (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to examine the correlational relationship between mastery of Qur’anic vocabulary and Arabic vocabulary skills among Islamic Senior High School (Madrasah Aliyah) students. The study is based on the assumption that the Holy Qur’an—with its vast lexical richness consisting of approximately 77,439 words distributed across 114 surahs—constitutes an exceptional educational source for acquiring eloquent Arabic vocabulary and developing learners’ linguistic competence.This study employed a quantitative correlational method and was conducted on a sample of Madrasah Aliyah students within an Islamic boarding school (pesantren) environment that integrates a Qur’anic memorization program with formal Arabic language instruction. Data were collected through two primary instruments: a Qur’anic vocabulary mastery test as the independent variable (X), and an Arabic vocabulary skills test as the dependent variable (Y). The data were statistically analyzed using SPSS through four stages: descriptive statistics, normality testing, hypothesis testing using the correlation coefficient, and coefficient of determination analysis.The findings revealed a statistically significant positive relationship between the two variables at the significance level of (α = 0.05), confirming that higher levels of Qur’anic vocabulary mastery positively influence students’ Arabic vocabulary skills. This relationship can be attributed to three main factors: first, Qur’anic vocabulary serves as a direct source of eloquent Arabic vocabulary; second, the systematic repetition of such vocabulary within the daily pesantren environment reinforces its retention in long-term memory; and third, emotional attachment to the Qur’an fosters strong intrinsic motivation to learn Arabic. The study concludes with several recommendations directed toward educators and policymakers, the most prominent of which is the need to systematically integrate Qur’anic vocabulary into Arabic language instruction while emphasizing semantic understanding rather than merely focusing on pronunciation and recitation aspects.